Mediation on trial: Ten verdicts on court-related ADR - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2004)
This article critically evaluates the development of court-related mediation by reference to the evolution of ADR practice and theory. The author explores the divergent approaches taken in different jurisdictions to the relationship between ADR and court-based processes while referring to some similar phases of development and the varied empirical examinations of process. The integration of ADR into the 'mainstream' dispute resolution culture is also explored from the perspective of the diversity versus consistency of process debates while reflecting upon the variations in ADR usage between inquisitorial and more adversarial legal systems.